Does natural root grafting make trees better competitors?. Issue 12 (27th September 2022) - Quer, Elodie; Helluy, Manon; Baldy, Virgine; DesRochers, Annie
Abstract : Natural root grafts (anastomoses) are morphological unions formed between roots of different trees. Common root systems allow translocation of water, nutrients and photosynthesis products between grafted trees, affecting their growth and their physiology. As carbohydrates are redistributed among grafted trees, the formation of a common root system could reduce the negative effect of intraspecific competition for light or soil resources within stands. The aim of this study was to investigate the role of root grafting on intraspecific competition and growth of balsam fir Abies balsamea . We studied inter‐tree relationships in three natural balsam fir stands of the boreal forest of Quebec (Canada) that contained an average 36% of grafted trees. At each stand, ring width and basal area of trees were measured using dendrochronology techniques. We used mixed linear models to test the effect of root grafting and intraspecific competition on annual basal area increment of trees. Trees before grafting had higher growth rates than trees once grafted. Thus, root grafting did not improve tree growth. Growth of grafted trees was more negatively affected by intraspecific competition than growth of non‐grafted trees. Thus, grafted trees cannot be considered as better competitors than non‐grafted trees. Under high intraspecific competition, growth of larger grafted trees was less affected than that of smaller trees suggesting that they were able to divert resources at their advantage within a union. Our study demonstrated that grafted trees acted on each other's growth and provides support for the idea that grafted trees respond to competition for resources more as a community rather than as individual trees.